Vrou as beeld van God: Vanaf die Reformasie tot die twintigste eeu - Dreyer, Yolanda (Hervormde teologiese studies, 2000)
Woman created in the image of God: From the Reformation through the twentieth century. The purpose of this artirle is to trace how woman has been represented in the history of theology, in the period stretching from the Renaissance to the feminist movement of the twentieth century, as the image of God. The focus is on the views of Luther, Calvin, Schleiermacher, Bonhoefer, Brunner and Barth. As far as the feminist movement is concerned, attention is paid in particular to the views of Daly, Coll and Ruether. The discussion proceeds from the presupposition that, apart from the master narrative (the patriarchal-hierarchical perspective), acounter-narrative (a more egalitarian perspective) is also present in the Bible.These two perspectives form the criterion according to which woman as image of God has been traced in the history of theology. The article has been written with a view to pastoral interaction with women.